Framing Media Accessibility Quality - Greco, Gian Maria; Jankowska, Anna (Journal of Audiovisual Translation, 2019)
The article provides an initial general overview of the status of quality in media accessibility. After highlighting some of the reasons behind the importance of addressing quality in media accessibility, the article discusses some problems that undermine the potential for full maturation of research and practices on quality. Then, it presents some possible solutions and proposes to use “media accessibility quality” to refer to the overarching problem of quality in media accessibility. The article concludes by listing a set of actions that constitutes a first draft of an agenda for the future of media accessibility quality.